Exploring the Role of Job Satisfaction and Work-Life Balance: A Study on the Mental Health Among Software Engineers - Aires, Maria Eulália; Migge, Lucas; Gama, Kiev; Lacerda, Aline (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3420, 2024)
Depression, anxiety and stress behaviors increasingly affect more people in different work contexts. These behaviors have significant impacts on personal and professional life, affecting quality of life and work performance. This research project aims to investigate the relationship between job satisfaction and the occurrence of symptoms of anxiety, depression and stress, in software engineering, and explore the organizational management of these activities in relation to employee well-being. The research used a mixed-method approach, combining qualitative and quantitative methods, including questionnaires and individual interviews. The sample was made up of 190 software engineering professionals, considering different workloads, lengths of experience, genders and companies. It revealed that 48.5% of participants presented moderate to very severe anxiety symptoms, 55.3% of depression for the same severity range and 53.8% of stress symptoms also for the same severity. Further linear regression analyses demonstrated that feeling valued, being able to cope with workload, and balancing professional and personal life were predictors for the emergence of symptoms of anxiety, depression, and stress. Finally, no significant differences were identified in the levels of anxiety, depression, stress and job satisfaction in relation to the loads held by the participants, but significant differences were noticed in relation to the variables listed above when comparing groups of different age ranges, severity of symptoms of anxiety, depression and stress. Groups with higher levels of symptoms demonstrated less balance between professional and personal life and a lower feeling of appreciation for the team, while for the group with fewer symptoms the result was the opposite.